Model validation and simulation studies on zoned and staged gas fired radiant tubes - XU Qian; FENG Jun-xiao; ZHOU Wen-hua; DONG Jie; HOU Yu (工程科学学报, 2016)
Experimental and numerical studies on double P-type radiant tubes were performed in this article firstly. According to the results, it is found that the deviations of parameters are within 1% except the NOx concentration with big error, indicating that the model has certain reliability. Based on this, the concept of air classification was applied to double P-type radiant tubes, a gas-fired radiant tube with branch pipe nozzles was introduced, and the corresponding mathematical and physical models were verified in this paper. Simulation results show that average flow velocities of the zoned and staged gas-fired radiant tube and the double P-type gas radiant tube are 25.8 m·s-1 and 21.0 m·s-1, and the thermal efficiencies are 65.9% and 64.2%, respectively. The highest wall surface temperature of the zoned and staged gas fired radiant tube is 1047 ℃, and the maximum wall temperature difference is 73 ℃, 15 ℃ less than that of the double P-type radiant tube. The gas average flow velocity increases after being zoned and staged, and the flue gas temperature and wall temperature of the straight pipe and backflow connection rises with a better uniformity of temperature.